Deconstruction of Masjid Architecture - Nazaruddin, Akhmad Farid (Proceedings of the International Conference on Green Technology; Vol 8 No 1 (2017): Proceedings of the International Conference on Green Technology, 2017)
Masjid are the basic architecture the place of Moslem. Westerns often calls it a Mosque. Ideally, with different context and era, there should be different Masjid architecture, with still guarding the main principals and values of Muhammad’s era Masjid. Different area should be different interpretation of a Masjid. Indonesia is the largest Moslem Country in the world. A good news for all Moslem in Indonesia is that the quantity of Masjid are increasing. While the bad news is, with the increasing numbers of Masjid, it does not followed with contextual designs. Most of them are just copy paste of Classical Arabic style of Masjid. Thus making the Masjid, architecturally “out of place”. Today, we live in a modern era with dynamic advance in technology and information. Moslem now required thinking differently while guarding their values. An idea emerges in Masjid Architecture, which required being different also. Thus hoping to attract more Jamaah, especially the young generation (who tend to think modern and contextual) to use the Masjid. This paper examined the steps needed to designs and applied a Deconstruction of Masjid Architecture, but keeping its values sacred. Hoping to create a more diverse and contextual Masjid architecture. An idea worth trying for applications in Masjid Architecture.